2017
DOI: 10.1111/ors.12299
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised clinical study on evaluation of platelet‐rich fibrin versus zinc oxide eugenol in the management of alveolar osteitis

Abstract: Purpose: The aim of this study was to evaluate the efficacy of plateletrich fibrin (PRF) in the management of alveolar osteitis and further compare the results with those of zinc-oxide Eugenol (ZOE). Materials and methods: A total of 40 patients with alveolar osteitis following extraction of mandibular molars were randomly divided into two groups on the basis of treatment, in which Group A patient's received PRF and Group B received ZOE as an obtundant dressing. Pain (VAS), degree of inflammation and number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(36 citation statements)
references
References 22 publications
0
33
0
3
Order By: Relevance
“…11,47 For quantitative analysis 13 articles were included, 9 articles about third molar 8, 25, 26, 28, 29, 32, 48-50 , 2 articles about sinus lift 35, 38 and 2 articles about dental implants 46, 51 . Seventeen articles were excluded and the reasons for exclusion were as follows: 4 non-randomized controlled clinical trial 52-55 ; 4 studies which outcomes of interest were not reported [56][57][58][59] ; 2 studies that used other PRF protocol 60,61 ; 1 study which did not test PRF 62 ; 1 retrospective study 63 ; 2 prospective studies 64,65 ; 1 study that used the same patients sample as other studies 66 ; 1 full text was not found 67 ; and 1 study was written in persa and not translated 68 . The value of Kappa was 0.84, thus it was considered an excellent agreement.…”
Section: Resultsmentioning
confidence: 99%
“…11,47 For quantitative analysis 13 articles were included, 9 articles about third molar 8, 25, 26, 28, 29, 32, 48-50 , 2 articles about sinus lift 35, 38 and 2 articles about dental implants 46, 51 . Seventeen articles were excluded and the reasons for exclusion were as follows: 4 non-randomized controlled clinical trial 52-55 ; 4 studies which outcomes of interest were not reported [56][57][58][59] ; 2 studies that used other PRF protocol 60,61 ; 1 study which did not test PRF 62 ; 1 retrospective study 63 ; 2 prospective studies 64,65 ; 1 study that used the same patients sample as other studies 66 ; 1 full text was not found 67 ; and 1 study was written in persa and not translated 68 . The value of Kappa was 0.84, thus it was considered an excellent agreement.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the medical history criteria, the study’s subject pool excluded pregnant and lactating women, heavy smokers (more than 10 cigarettes per day), and people using illicit drugs. The study-subject selection criteria, clinical, and analytical methods mirrored previous research to allow comparison [27].…”
Section: Methodsmentioning
confidence: 99%
“…This is in agreement with previous studies where the common age group was reported in the range of 30 to 40 years. 14 , 16 However, some studies have reported a peak incidence in the second decade. 31 , 32…”
Section: Discussionmentioning
confidence: 99%
“…5. Estimation of sample size 16 where Z ∞ = 1.96 for ∞ = 0.05, Z β = 0.84 for β = 0.20, Δ = μ T − μ C (difference in mean). σ = SD.…”
Section: Patient and Methodsmentioning
confidence: 99%
See 1 more Smart Citation